Lower immune senescence of T cell subsets among virologically suppressed Chinese men who have sex with men living with HIV in comparison with those ART naive - Li Li; Fengting Yu; Siyuan Yang; Hui Li; Yunxia Tang; Chengjie Ma (BMC Infectious Diseases)
Abstract Background Immune senescence can occur in untreated HIV infection and is partially reversible with effective antiretroviral therapy (ART). Here, we investigated the differences in immune senescence of T cell subsets among Chinese men who have sex with men (MSM) living with HIV virologically suppressed on ART compared to those ART-naive. Methods A cohort of MSM living with HIV with different disease courses was included, untreated viral non-controllers (n = 26) and those on ART (n = 30). The percentages of naive, central memory (TCM), effector memory (TEM), and terminally differentiated memory (TemRA) subsets of CD4 and CD8 T cells were studied, along with markers of senescence (CD28-CD57+) and activation (HLA-DR). Telomere length of naive and memory CD8 T cells was quantified by real-time PCR. The correlation between senescent CD4 and CD8 T cell subsets and CD4 and CD8 cell counts was analyzed with the Spearman rank correlation. Results Compared with the ART-naive group, the percentage of senescent cells (CD28- CD57+) in total CD8 T cells was significantly lower in the ART group (P < 0.01). Significant differences were observed among CD8 T cell subsets, but not in CD4 T cell subsets (P < 0.05). In the ART group, the percentage of senescent cells (CD28-CD57+) in TN and TCM subsets of both CD4 and CD8 T cells was lower (all P < 0.05). HLA-DR expression was significantly lower in all CD4 and CD8 T cell subsets except TEMRA subset (P < 0.05). The telomere length of CD8 T cell subsets did not differ significantly between the two groups. The percentage of senescent naive CD4 T cells was inversely correlated with CD4 T cell counts (r = -0.42, P = 0.0343), while the percentage of senescent naive CD8 T cells was positively correlated with CD8 T cell counts (r = 0.47, P = 0.0161) in the ART-naive group, but not in the ART group. Conclusions Virologically suppressed MSM living with HIV exhibit lower immune senescence of T cell subsets, which is more pronounced for CD8 cell subsets. The percentage of senescent naive T cells is significantly correlated with clinical immunity based on CD4 and CD8 T cell counts.